(untitled) (diségno, 2019)
This book is the final development of a scientific research work that began some years ago when Silvia Masserano, author of this volume and involved in teaching activity at the University of Trieste, carried out her PhD Thesis, entitled Prospettive architettoniche dei teleri di Paolo Caliari, detto il Veronese. Analisi, comparazione e restituzione. The thesis was recently awarded with two prizes: the Menzione Gaspare De Fiore 2017, by the Unione Italiana per il Disegno, and the Premio tesi di Dottorato EUT, by Edizioni Università di Trieste. The last award has allowed her to publish this book with the funding and institutional support of her University